2011
DOI: 10.1890/10-0234.1
|View full text |Cite
|
Sign up to set email alerts
|

Indirect benefits of symbiotic coccoids for an ant-defended myrmecophytic tree

Abstract: Abstract. The net benefits of mutualism depend directly on the costs and effectiveness of mutualistic services and indirectly on the interactions that affect those services. We examined interactions among Cordia alliodora myrmecophytic trees, their symbiotic ants Azteca pittieri, coccoid hemipterans, and foliar herbivores in two Neotropical dry forests. The tree makes two investments in symbiotic ants: it supplies nesting space, as domatia, and it provides phloem to coccoids, which then produce honeydew that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(76 citation statements)
references
References 27 publications
2
72
1
1
Order By: Relevance
“…The heterogeneous distribution of resources over different parts within a certain scale can shape the outcome of ant-plant interaction. In the direct ant-plant interaction, some high-quality rewards for ants only occur on young leaves, twigs, or larger segments within a tree (Miller 2014;Pringle, Dirzo, & Gordon 2011). In some cases, ant densities on larger trees are lower than the densities on smaller ones, which can lead to the varied effects of ants on plants on different-sized trees (Palmer & Brody 2013;Palmer et al 2010;Pringle, Dirzo, & Gordon 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The heterogeneous distribution of resources over different parts within a certain scale can shape the outcome of ant-plant interaction. In the direct ant-plant interaction, some high-quality rewards for ants only occur on young leaves, twigs, or larger segments within a tree (Miller 2014;Pringle, Dirzo, & Gordon 2011). In some cases, ant densities on larger trees are lower than the densities on smaller ones, which can lead to the varied effects of ants on plants on different-sized trees (Palmer & Brody 2013;Palmer et al 2010;Pringle, Dirzo, & Gordon 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Grover et al (2007) found that both activity levels and intraspecific aggression of L. humile were higher for lab colonies that were fed a diet rich in carbohydrates than under a proteinrich diet. Similarly, Pringle et al (2010) showed that native plant-inhabiting ants in a neotropical lowland rainforest were more aggressive towards plant-feeding herbivores when fed a diet rich in carbohydrates. However, Kay et al (2010) examined the aggression exerted by L. humile towards heterospecific ants and found no influence of diet, although carbohydrate-rich diets resulted in greater colony growth (a densitymediated effect).…”
Section: Effects Of Nectar Subsidies On Ant Aggressionmentioning
confidence: 97%
“…Cordia alliodora is found throughout the neotropics, from Mexico to Argentina, and the quality of ant defence varies throughout this range [52]. Ants are particularly good defenders at the Chamela site studied here [11]. Interestingly, A. atkinsoni, which was by far the most abundant bruchid seed predator in this study, is endemic to Jalisco, Mexico [35], and is replaced by different species of Amblycerus farther south [36].…”
Section: Discussionmentioning
confidence: 80%
“…Because a given ant colony associates with a single plant throughout its lifetime, but partners disperse separately, symbiotic ant-plant mutualisms are predicted to be good examples of 'short-term' (within-generation) partner fidelity feedback [4]. Consistent with this prediction, recent empirical studies of ant-plant symbioses have demonstrated positive feedback between plant rewards and ant defence [7,10,11]. However, ants may reduce herbivory or even increase plant growth without necessarily increasing plant fitness [12], and direct evidence that ants increase plant reproductive output is relatively scarce [but see 13 -16].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation